Idealizm a sceptycyzm - Zeidler, Kurt Walter (Folia Philosophica, 2018)
The text refers to an interesting, since ancient and important, epistemological problem of justification of our beliefs, and in particular, the so-called final justification. To the recent methodological and epistemological literature, for example, the so-called Münchhausen trilemma of Hans Albert is known. The author argues that this trilemma can be found already in the ancient philosophy, with which the question of the effectiveness of a dispute with skepticism is connected. The most interesting and original is the view of the relationship between idealism and skepticism from the perspective of history of philosophy, philosophy of science and transcendental philosophy.